Viability of part cargoes in tramp shipping company’s routing and scheduling decisions - Saari, Jessica (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2016)
Operational excellence of individual tramp shipping companies is important in today’s market, where competition is intense, freight revenues are modest and capital costs high due to global financial crisis, and tighter regulatory framework is generating additional costs and challenges to the industry. This thesis concentrates on tramp shipping, where a tramp operator in a form of an individual case company, specialized in short-sea shipping activities in the Baltic Sea region, is searching ways to map their current fleet operations and better understand potential ways to improve the overall routing and scheduling decisions. The research problem is related to tramp fleet planning where several cargoes are carried on board at the same time, which are here systematically referred to as part cargoes. The purpose is to determine the pivotal dimensions and characteristics of these part cargo operations in tramp shipping, and offer both the individual case company and wider research community better understanding of potential risks and benefits related to utilization of part cargo operations. A mixed method research approach is utilized in this research, as the objectives are related to complex, real-life business practices in the field of supply chain management and more specifically, maritime logistics. A quantitative analysis of different voyage scenarios is executed, including alternative voyage legs with varying cost structure and customer involvement. An on-line-based questionnaire designed and prepared by case company’s decision group again provides desired data of predominant attitudes and views of most important industrial customers regarding the part cargo-related operations and potential future utilization of this business model. The results gained from these quantitative methods are complied with qualitative data collection tools, along with suitable secondary data sources. Based on results and logical analysis of different data sources, a framework for characterizing the different aspects of part cargo operations is developed, utilizing both existing research and empirical investigation of the phenomenon. As conclusions, part cargoes have the ability to be part of viable fleet operations, and even increase flexibility among the fleet to a certain extent. Naturally, several hinderers for this development is recognized as well, such as potential issues with information gathering and sharing, inefficient port activities, and increased transit times.